Political Empowerment of Women in Russia:Discourses and Strategies - Popkova, Ludmila (Sociologija. Mintis ir veiksmas, 2005)
The article analyzes public discourses on political leadership of women in the post-communist Russia. Based on her sociological research the author differentiates two main strategies of female politicians and women’s organizations. The first “professional” group of activists considers women’s interests or women’s rights issues as marginal for their democratic agenda. The second “maternalistic” strategy insists on the essentialist women’s political “predestination” to be responsible only for social and family policy. The analysis of these discourses gives the understanding of the perspectives for political empowerment of Russian women in the context of democratic transition.